ANALISIS ISI PESAN EDUKASI SERIAL ANIMASI “RIKO THE SERIES” SEBAGAI NILAI KARAKTER PEDULI SOSIAL ANAK USIA DINI - Zahro, Ida; ., Mutiah (Universitas Negeri Surabaya, 2025)
Technological advances are currently developing very rapidly, especially in the fields of communication and information. Many people still don't realize that there are many social media that provide educational content for teaching materials. YouTube is one of the social media that has become a learning tool, one of which is the YouTube channel Riko The Series. In the animated series Riko The Series there are also several educational messages contained in it, one of which is the Character Value of Social Care. The research method used is a type of discourse analysis research developed by Teun A. Van Dijk, with a qualitative descriptive approach. Researchers will examine the content of educational messages in the animated series Riko The Series which contain social caring character values ​​using Teun A. Van Dijk's discourse analysis model, namely in Episodes 1, 2, 3, 8, and 15. The results of the research and discussion can be drawn conclusions Overall, in Episodes 1, 2, 3, 8, 15 there are social care character values ​​consisting of: a). Help, b). Apologize to each other, c). Caring for Others, d). Remind each other, e). Forgive. Through Teun A. Van Dijk's discourse strategy model, the author finds that the information in each sentence contained in the dialogue of the animated series